The implementation of sustainability practices among manufacturing small and medium enterprise (SMES): A review of literature - Yong, Voon Khai; Abu, Noor Hidayah; Hashim, Rushanim (2017)
Environmental concerns and conscious become a major awareness among government and society in many countries.Therefore, SMEs have to find ways to adopt and implement sustainable manufacturing practice in their operations.A sustainable approach could reduce firm’s negative reputation and increases quality of product, healthy and profit. SMEs represent majority business unit and contribute for economic growth in Malaysia.At the same time SMEs pose serious environmental problems due to their high number and cumulative effect. It is important for SME to implement sustainability practices in order to protect the environment. However, most of previous studies in sustainability practices have given full attention to larger organization instead of SMEs.SMEs are required to understand the implementation sustainability practices from SMEs context, rather than follow large organization understanding. The objectives of this study are to determine the critical success factors (CSF) and obstacles for sustainable practices implementation among manufacturing SMEs.The method used in this study is conceptual review of previous literature in sustainable and SMEs area of research.The finding of this paper has identified 10 CSF and 8 obstacles in implementing the sustainable practices.The finding from this study could provide some suggestions and guidelines for SMEs owner and manager in assessing their initiative to implement sustainable practices in organization.Besides the finding also could be a source and fundamental guideline for future study in developing of a sustainable practices implementation framework for Malaysian manufacturing SMEs.